Improving Digital Literacy through Training on the Use of Technology-Based Learning Applications in Elementary Schools - Afandi, Ahmad; MA, Wajnah; Pradana, Pascalian Hadi; Nurtamam, Mohammad Edy; Mahmudah, Siti (Abdimas Indonesian Journal, 2024)
This study aims to analyse strategies for improving digital literacy in primary school students through training in the use of technology-based learning applications. Digital literacy is an essential skill in today's digital era, where the ability to understand and use technology effectively is one of the keys to educational success. Using the literature study method, this research examines various educational technology approaches and applications that can improve digital literacy. The findings show that training in the use of learning applications, such as e-learning platforms, educational games and video-based applications, can improve students' digital literacy skills. In addition, the involvement of teachers as facilitators in the technology-based learning process is a key factor in the success of the training.